HUBUNGAN ANTARA PERILAKU K3 DAN DOSIS RADIASI PEKERJA DI PUSAT TEKNOLOGI RADIOISOTOP DAN RADIOFARMAKA (PTRR) BATAN SERPONG - Lena Tresnawati; Hanifa Maher Denny; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
BATAN Serpong Radioisotopes and Radiopharmaceuticals Technology Center (PTRR) is a business unit conducting utilization of nuclear energy in thefields of radioisotope and radiopharmaceutical. This work unit has radiation workers who potentially recieve a radiation dose in a certain amount. The radiation dose which is received by radiation workers may be caused by their behaviour when working because the behaviour is a reflection of the knowledge, attitudes, and practices of a person. The purpose of this study was to analyze there is any relationship between knowledge, attitudes, and practices which related to radiation protection principles, and their relation to the radiation doses which received by workers in PTRR BATAN Serpong.This study was a quantitative design in the form of a explanatory cross sectional. The samples in this study was 52 radiation workers of Radioisotopes, Radiopharmaceuticals, as well as Occupational Safety and Waste Management were selected based on purposive sampling technique. Data analysis used Spearman Rank test with a level of 95%. The results showed that the knowledge, attitude, and practice of radioation workers in PTRR BATAN Serpong classified as good, and the radiation dose which received by workers was still below the dose limit value. Statistical analysis showed that knowledge of radiation protection principles related to the radiation dose with weak and negative relationship (p-value = 0,017, ρ= -0,331), and practices of radiation protection principles related to the radiation dose with strong and negative relationship (p-value = 0,001, ρ= -0,521). Menwhile, attitudes of radiation protection principles did not related with radiation dose (p-value = 0,774). We recommended that the management give reward and punishment to radiation workers which related to radiation protection principles.